Technical and Economic Aspects of Electric Energy Storage in a Mine Shaft—Budryk Case Study - Jarosław Kulpa; Paweł Kamiński; Kinga Stecuła; Dariusz Prostański; Piotr Matusiak; Daniel Kowol; Michał Kopacz; Piotr Olczak (Energies, 2021)
The transformation of the energy sector towards an increased share of renewable energy sources in the energy mix requires attention in the area of electricity storage. Renewable energy sources (photovoltaics or wind energy) are marked by the intermittency of electricity production and require the construction of energy storage to adapt the energy supply to the demand, providing greater stability. The authors focused on verifying the solution of gravitational energy storage in existing shafts of hard coal mines in Poland. The issue is significant for Poland, as a country with an extensive mining infrastructure, which is searching for new scientific and practical solutions to utilize disused mining shafts for new purposes. In the analysis, the focus was on one shaft located within the Upper Silesian Coal Basin (Górnośląskie Zagłębie Węglowe), maintained for the drainage of the neighboring deposit. The article presents the calculation of energy that can be stored and an analysis of the effectiveness of energy storage in the shaft. The basic assumption of the analysis was 1 cycle of work per day (charging and discharging) in order to use the effect of low prices at night and high prices during peak hours (according to Towarowa Giełda Energii (TGE) quotations). Although energy storage already functions around the world, the studied case is new, because it refers to the usage of existing shafts which makes it a non-investment case. The results of the study showed that the obtained economic effects of the analyzed solution are low, therefore there is no economic justification of activities related to its implementation, taking into account the current price conditions.